Kawin Tangkap (Pakondong) di Kaji Dari Undang-Undang Nomor 1 Tahun 1974 tentang Perkawinan di Desa Ana Engge Kecamatan Kodi Kabupaten Sumba Barat Daya (Doktrin: Jurnal Dunia Ilmu Hukum dan Politik, 2025)
This study discusses the practice of "capture marriage" (pakondong) still carried out in Ana Engge Village, Kodi District, West Sumba Regency, as part of the local tradition. Capture marriage is a practice where a man "captures" his prospective wife without the consent of the woman or her family. This practice has been ongoing for a long time and is considered part of local culture. However, when viewed from the perspective of national law, particularly Law No. 1 of 1974 on Marriage, this practice raises controversy. The law emphasizes that marriage must be conducted with the free consent of both parties, as stated in Article 6, Paragraph 1, which asserts that a marriage is only valid if both parties agree. This research uses an empirical juridical method, with interview techniques and literature studies, to examine the legality of capture marriage under positive law. The results show that capture marriage contradicts the basic principles of a valid marriage because it does not meet the requirement of free consent from both parties involved. Furthermore, capture marriage is also considered a violation of women's human rights, as women should have the right to choose their life partners without coercion or pressure. This practice also degrades women's dignity, as their rights as independent individuals to make their own choices should be respected. The conclusion of this study is that capture marriage cannot be justified under national law because it contradicts the principle of free and mutual consent. Therefore, efforts are needed from various parties, including the government, law enforcement, customary leaders, and society, to provide education on the importance of consent in marriage. Additionally, the modernization of customary law is crucial to align it with constitutional values and human rights, ensuring the protection of women's rights and promoting the development of a more just and equitable culture.